Method and device for preparing cement-based building material by pre-carbonizing carbide slag with carbon dioxide
By using the carbon dioxide pre-carbon calcium carbide slag method in the carbon sequestration technology of calcium carbide slag, the problem of low-concentration carbon dioxide flue gas utilization is solved, the carbon sequestration efficiency and energy efficiency are improved, and cement infrastructure materials with high mechanical properties are produced.
Patent Information
- Application Number
- CN202510220681.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-27
AI Technical Summary
The existing calcium carbide slag carbon sequestration technology cannot directly utilize the low-concentration carbon dioxide flue gas recovered in industrially, resulting in low carbon sequestration efficiency and high energy consumption.
The carbon dioxide pre-carbon calcium carbide slag is used to mix the calcium carbide slag with water and seal it and stand still, and then carbon sedimentation gas is introduced into the calcium carbide slag suspension under a stirring state to conduct carbon sediment slurry to produce a pre-carbon calcium carbide slurry, and then mixed with the cement slurry dry material to form carbon curing.
It improves the carbon sequestration efficiency of calcium carbide slag, reduces energy consumption, and can directly utilize low-concentration carbon dioxide flue gas, realizes the efficient utilization of industrial solid waste and waste gas, and the cement-based building materials produced have higher mechanical properties.
Smart Images

Figure CN119682035A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon dioxide fixation, and more specifically to a method and device for preparing cement-based building materials by using carbon dioxide precarbonized carbide slag. Background Art
[0002] As the emission of greenhouse gas CO2 increases, carbon reduction strategies have been put on the agenda. Most researchers use building materials for carbon curing to achieve the purpose of carbon reduction. Carbon curing is a method in which CO2 enters the cement-based material from the outside to undergo a carbon solidification reaction to achieve carbon sequestration. In recent years, direct mixing of CO2 with cement-based materials has become a highly-regarded internal carbon fixation technology. Its core technology is to inject CO2 captured from the industrial end into the mixture during the mixing process of concrete, mortar, etc., so that CO2 reacts with silicate cement clinker minerals and their hydration products to produce carbon mineralization reactions, thereby improving product performance and reducing product carbon footprint. However, the use of carbon curing technology and CO2 direct mixing of cement-based materials alone cannot achieve a significant carbon fixation effect. The combined use of both methods can increase the carbon fixation rate to a certain extent. Therefore, the method of using CO2 directly to mix cement-based materials in conjunction with carbon curing is more conducive to carbon fixation. In the early stage, the method of mixing cement-based materials with CO2 is used for internal carbon fixation. In the early stage, CO2 reacts with the hydration product Ca(OH)2 in the cement-based materials to generate CaCO3. CaCO3 exists as fine particles as seeds, which promotes the carbon solidification reaction in the later carbon curing process. Therefore, it is of great significance to develop a new carbon fixation method for mixing cement-based materials with CO2.
[0003] Calcium carbide slag is a kind of industrial waste residue and a by-product of the hydrolysis of calcium carbide (CaC2) to produce acetylene. Its main component is Ca(OH)2 (content>80%), and it has great potential for mineralization and fixation of CO2. my country is a major emitter of calcium carbide slag solid waste. Therefore, harmless treatment of calcium carbide slag and efficient resource utilization are the only way to solve the environmental pollution problem in the calcium carbide industry.
[0004] Patent CN115215586A discloses a method for preparing autoclaved aerated concrete bricks by wet grinding and carbon fixation of carbide slag. In this method, carbide slag is wet milled after adding water, and carbon dioxide is introduced during the ball milling process for carbon fixation; after carbon fixation, the obtained carbon fixation slurry is mixed with cement, gypsum, lime, and fine aggregate (tailings) and stirred, and then water and aluminum powder are added to obtain a mixed mortar; finally, the mixed mortar is formed and carbon cured to obtain a concrete brick. Although industrial solid waste carbide slag has been utilized, this method requires the introduction of carbon dioxide for carbon fixation during the wet ball milling process, which has low carbon fixation efficiency, high mechanical energy consumption, and requires the introduction of a higher concentration (40% to 60%) of carbon dioxide to achieve effective carbon fixation. However, the carbon dioxide concentration in the flue gas discharged in industrial production is only 20%, which cannot be directly used in this method. Therefore, it is necessary to further improve the carbon fixation of carbide slag to reduce the energy consumption of carbide slag carbon fixation and improve the carbon fixation efficiency so that low-concentration carbon dioxide can be directly used for carbon fixation. Summary of the invention
[0005] To this end, the technical problem to be solved by the present invention is to provide a method and device for preparing cement-based building materials using carbon dioxide pre-carbonized carbide slag, so as to solve the technical problem that the existing carbide slag carbon fixation cannot directly utilize the low-concentration carbon dioxide flue gas recovered industrially. The present invention uses carbide slag for early pre-carbonization and later carbonization maintenance, which not only solves the problem of carbon emission reduction, but also effectively utilizes industrial solid waste carbide slag. If it is applied in large quantities in practice, it will produce good economic benefits.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing cement-based building materials using carbon dioxide pre-carbonized carbide slag comprises the following steps: Step (1), mixing carbide slag with water and sealing and standing to obtain a carbide slag suspension; Step (2), in a sealed state, introducing a carbon-fixing gas containing carbon dioxide into the carbide slag suspension while stirring to carry out a carbon-fixing reaction, and after the carbon-fixing reaction is completed, a pre-carbonized carbide slag slurry is obtained; Step (3), mixing the pre-carbonized carbide slag slurry with the cement slurry dry material to obtain carbide slag cement slurry; Step (4), injecting carbide slag cement slurry into a mold for molding, and obtaining carbide slag cement blank after demoulding; Step (5), placing the carbide slag cement blank in a carbon curing box for carbon curing, and obtaining a cement-based building material product after the carbon curing is completed.
[0007] The present invention utilizes carbon dioxide pre-carbonized carbide slag to prepare a cement-based building material. In the process of premixing carbide slag, carbon dioxide is introduced to prepare pre-carbonized carbide slag slurry, thereby avoiding the problem of incompatibility between carbide slag and cement caused by directly adding carbide slag. The prepared pre-carbonized carbide slag slurry is then mixed with cement paste to prepare carbide slag cement blank. Finally, the carbide slag cement blank is subjected to carbon curing to obtain a finished cement-based building material. The CaCO3 generated in the process of premixing carbide slag can promote the carbon solidification reaction in the carbon curing process as a crystal seed. In the whole process, the green concept of solid waste carbon fixation is realized through the utilization of carbide slag waste and two technical means of internal and external carbon fixation, which makes a significant contribution to protecting the environment, improving economic benefits, enhancing mechanical properties and alleviating the greenhouse effect.
[0008] In the method for preparing cement-based building materials by using carbon dioxide to precarbonize carbide slag, in step (1), the particle size of the carbide slag is in the range of 5 to 75 μm; the mass ratio of the carbide slag to water is 1:(1.5 to 5); and the sealed standing time is 10 to 20 minutes. The carbide slag in the particle size range can be mixed with water in a mass ratio of 1:(1.5 to 5) to form a carbide slag suspension with a moderate concentration. After 10 to 20 minutes of sealed standing, the calcium hydroxide (CH) in the carbide slag can be dissolved and dispersed in the water as much as possible, which is conducive to the subsequent carbonization reaction.
[0009] If the particle size of carbide slag is too large, the calcium hydroxide in the form of "lime milk" in the carbide slag suspension cannot be replenished and dissolved into the water in time to participate in the carbon fixation reaction during the carbon fixation process, thus affecting the carbon fixation effect. If the particle size of carbide slag is too small, the generated calcium carbonate particles will wrap the calcium hydroxide and affect its participation in the carbon fixation reaction.
[0010] If the ratio of carbide slag to water in the carbide slag suspension exceeds the above range, for example, the amount of carbide slag is too large, the "lime milk" in the formed carbide slag suspension will be denser, and the calcium hydroxide in the "lime milk" will not be easily released quickly during the carbon fixation reaction, thereby affecting the efficiency of the carbon fixation reaction; and, excessive carbide slag will also affect the strength of the final cement-based building materials; but if the amount of carbide slag is too small, the introduced carbon dioxide gas will find it difficult to capture sufficient calcium hydroxide and will not react fully, thereby affecting the utilization rate of carbon dioxide in the carbon fixation gas.
[0011] The present invention controls the ratio of carbide slag in a specific particle size range to water in the carbide slag suspension within the above range, so that a part of the calcium hydroxide in the carbide slag can be fully dissolved in the water, and the other part can be combined with water to temporarily form "lime milk" with moderate density. During the carbon fixation reaction, the calcium hydroxide in the "lime milk" can be continuously and rapidly released into the water to participate in carbon fixation as the calcium hydroxide in the water is consumed. This can not only significantly improve the carbon fixation efficiency of the carbide slag, but also allow the introduced carbon fixation gas to have sufficient carbon fixation reaction opportunities, so that the carbon dioxide in the carbon fixation gas with a low carbon dioxide concentration can also be fully utilized, and the flue gas recovered from the cement plant or steel plant can be directly utilized to avoid the use of high-concentration carbon dioxide.
[0012] In the above method for preparing cement-based building materials using carbon dioxide pre-carbonized carbide slag, in step (1), the particle size range of the carbide slag is 10 to 40 μm; the mass ratio of the carbide slag to water is 1:2.5; and the sealed standing time is 10 minutes. The purpose of the sealed standing is to dissolve as much calcium hydroxide in the carbide slag as possible, thereby increasing the pH of the carbide slag suspension. At this time, it is easier to react when carbon dioxide is introduced, which is beneficial to improving the carbon fixation efficiency and the utilization rate of carbon dioxide in the carbon fixation gas; if the static sealing is not performed, and the carbon fixation gas containing CO2 gas is immediately introduced for carbon fixation reaction, the CO2 in the carbon fixation gas will be more soluble in water than calcium hydroxide, thereby rapidly reducing the pH value of the carbide slag suspension. The acidic environment formed in this way is more unfavorable for the carbonization reaction, thereby being unfavorable for the full utilization of low-concentration carbon dioxide carbon fixation gas.
[0013] In the above method for preparing cement-based building materials using carbon dioxide pre-carbonized carbide slag, in step (2), during the carbon fixation reaction: the stirring rate is 600-800 rpm; the flow rate of the carbon fixation gas is 1.5-2.5 L / min; the carbon fixation reaction is carried out at room temperature; the carbon fixation reaction time is 10-30 min; and the volume concentration of carbon dioxide in the carbon fixation gas is greater than or equal to 20%.
[0014] During the carbon fixation reaction, if the stirring rate is too low, the CO2 gas will not be evenly distributed in the carbide slag suspension, affecting the contact effect between the carbide slag and CO2, resulting in insufficient CaCO3 generation, which not only affects the carbon fixation efficiency, but also affects the strength and hardening performance of the cement slurry; if the stirring rate is too high, the CO2 bubbles will burst too quickly, thereby reducing the dissolution efficiency of CO2 and affecting the uniformity of the reaction. If the flow rate of the carbon fixation gas is too large, the excess CO2 will be directly discharged before it can react, greatly reducing the utilization rate of CO2; if the flow rate of the carbon fixation gas is too small, the pre-carbonization effect will be reduced, and the purpose of carbon fixation and improving compatibility with cement cannot be achieved. If the pre-carbonization reaction time is too short, the carbonization reaction will be incomplete, insufficient CaCO3 will not be generated, the pH value of the calcium carbide slag suspension will still be high, the carbon fixation will be less, and the compatibility with cement will not be improved; if the pre-carbonization time is too long, the generated CaCO3 particles will accumulate. When there are too many CaCO3 particles, since the CaCO3 particles mainly play a filling role, and do not participate in the hydration reaction like Ca(OH)2, too many CaCO3 particles will cause the pore structure of the cement slurry to be not dense enough, which will eventually affect the strength and density of the cement. The present invention can effectively improve the utilization rate and carbon fixation efficiency of carbon dioxide by controlling the carbon fixation gas flow rate, stirring rate and carbon fixation time in the carbon fixation reaction process within the above range, so that the carbon dioxide in the carbon fixation gas of low concentration carbon dioxide is fully utilized, and at the same time, it provides a basis for the subsequent cement-based building materials with good mechanical properties.
[0015] In the above method for preparing cement-based building materials using carbon dioxide pre-carbonized carbide slag, in step (2), during the carbon fixation reaction: the stirring rate is 600 rpm; the flow rate of the carbon dioxide gas is 2.0 L / min; the carbon fixation reaction time is 20 min; the carbon fixation gas is carbon dioxide gas with a purity of 99.99% by volume after liquefaction and purification; or, the carbon fixation gas is a mixture of carbon dioxide gas with a purity of 99.99% by volume after liquefaction and purification and air; or, the carbon fixation gas is flue gas recovered from a cement plant and / or a steel plant.
[0016] Compared with the wet ball milling carbon fixation method in the background technology patent CN115215586A, the present invention has the following advantages: (1) faster reaction rate: when CO2 is introduced into the carbide slag suspension, the reaction is more rapid. During the carbon fixation process, stirring at a stirring rate of 600 rpm will make the carbide slag suspension in a flowing state, which is conducive to the rapid reaction of CO2 and calcium hydroxide. In addition, due to the rapid reaction, the reaction releases heat more rapidly, the temperature rises rapidly, and the reaction is further promoted. (2) higher economic benefits: carbide slag in a specific particle size range is mixed with water in a specific mass ratio, and then sealed and left to stand for a certain period of time to form a carbide slag suspension, and a specific stirring rate and solidification are used. By introducing carbon-fixing gas into the carbide slag suspension at a high carbon gas flow rate, the low-concentration carbon dioxide gas (the volume concentration of carbon dioxide can be greater than or equal to 20%) can be fully utilized. Therefore, this process is more conducive to industrial docking. For example, the flue gas recovered from cement plants or steel plants has a CO2 volume concentration of about 20%. It can be directly used for carbide slag carbon fixation without treatment, and does not require complex mechanical equipment, so the cost is low. (3) Low energy consumption: The carbon fixation method of introducing CO2 into the carbide slag suspension is more energy-saving and does not require high mechanical energy input. (4) The operation steps are simple: it is only necessary to mix water and carbide slag to prepare carbide slag suspension, and then mix carbide slag suspension with cement slurry dry material, which is easy to operate.
[0017] In addition, when preparing carbide slag cement slurry, the present invention only needs to mix the pre-carbonized carbide slag slurry obtained after carbon fixation with the cement slurry dry material. In this process, there is no need to add water for the second time to prepare the pure slurry. Therefore, there are fewer bubbles, denser pores, and the resulting cement-based building materials have higher strength and a wider range of applications.
[0018] In the above method for preparing cement-based building materials using carbon dioxide precarbonized carbide slag, in step (3), the mass ratio of precarbonized carbide slag slurry to cement slurry dry material is 1: (0.8-1.5); the mixing and stirring time is 3-10 minutes; the cement slurry dry material is a composite material with cement as a gelling material; and the preparation method of the cement slurry dry material is: mixing and stirring the raw material components of the cement slurry dry material according to the designed proportion for 3-5 minutes. The present invention controls the amount ratio of precarbonized carbide slag slurry to cement slurry dry material so that the water-cement ratio of the finally prepared carbide slag cement slurry is within a suitable range, so that the carbide slag cement slurry has a relatively ideal fluidity, avoids the occurrence of segregation in the process of preparing cement-based building materials, affects the uniformity of the carbide slag cement slurry, causes stratification and uneven hardening effects, and at the same time ensures that the cement is fully hydrated, so that the finally prepared cement-based building materials have ideal mechanical properties.
[0019] In the above method for preparing cement-based building materials using carbon dioxide precarbonized carbide slag, in step (3), the mass ratio of precarbonized carbide slag slurry to cement slurry is 1:1.14; the mixing time is 3 minutes; the cement slurry dry material is cement, cement mortar dry material (mixed by cement and sand in a mass ratio of 1:3 to 6) or concrete dry material (mixed by cement, sand and gravel in a mass ratio of 1:2 to 3:3 to 6); the mixing time when preparing the cement slurry dry material is 3 minutes; and the cement is ordinary Portland cement with a strength grade of 42.5.
[0020] In the above method for preparing cement-based building materials using carbon dioxide pre-carbonized carbide slag, in step (4), the carbide slag cement slurry molding conditions are: demolding after standing for 24 hours at room temperature and pressure; in step (5), the carbon curing conditions are: carbon dioxide volume concentration of 20±3%, relative humidity of 70±5%, temperature of 20±3°C; and carbon curing time is 7 to 28 days. During the carbon-oxygen curing process: if the carbon dioxide concentration is too high, the carbonization reaction of the surface layer of the specimen will be too fast, affecting the carbonization reaction of the inner layer of the specimen, thereby affecting the strength of the specimen; if the carbon dioxide concentration is too low, Ca(OH)2 cannot be fully converted into CaCO3, lacking sufficient filling effect and seed effect, and thus failing to effectively improve the microstructure and strength of the specimen; if the relative humidity is too high, there will be too much moisture on the surface of the specimen, which will cause the hydration reaction to proceed rapidly. The exothermic expansion of the hydration reaction will cause the pores to increase, affecting the density of the specimen; if the humidity is too low, it will affect the hydration process of the cement, resulting in incomplete hardening of the cement, thereby reducing the ultimate strength of the specimen; if the temperature is too high, it will accelerate the hydration reaction of the cement, causing the cement slurry to generate too much heat, resulting in cracks on the cement surface, affecting its ultimate strength and durability; when the temperature is too low, the cement hydration reaction rate will be significantly reduced, resulting in a delay in the cement hardening process, affecting the strength development of the specimen. Under the above-mentioned carbon curing conditions of the present invention, the purpose of "making full use of the calcium carbonate generated by pre-carbonization as a seed for carbon fixation reaction in a relatively low concentration of carbon dioxide environment, and further improving the mechanical properties of cement-based building materials" can be achieved.
[0021] In the above method for preparing cement-based building materials using carbon dioxide precarbonized carbide slag, in step (1), the particle size of the carbide slag is in the range of 10 to 40 μm; the mass ratio of the carbide slag to water is 1:2.5; and the sealed standing time is 10 minutes; In step (2), during the carbon fixation reaction: the stirring rate is 600 rpm; the flow rate of the carbon fixation gas is 2.0 L / min; the carbon fixation reaction is carried out at room temperature; the carbon fixation reaction time is 20 min; the carbon fixation gas is flue gas recovered from a cement plant and / or a steel plant, and the volume concentration of carbon dioxide in the flue gas is 20%; In step (3), the mass ratio of pre-carbonized carbide slag slurry to cement slurry is 1:1.14; the mixing time is 3 minutes; the cement slurry is ordinary Portland cement with a strength grade of 42.5; In step (4), the carbide slag cement slurry is formed under the following conditions: standing at room temperature and pressure for 24 hours before demoulding; In step (5), the carbon curing conditions are: the volume concentration of carbon dioxide is 20%, the relative humidity is 70%, and the temperature is 20° C.; and the carbon curing time is 28 days.
[0022] A device for preparing cement-based building materials by using carbon dioxide to pre-carbonize carbide slag, comprising a carbon dioxide storage container, a primary mixing container, a waste gas absorption tank, a secondary mixing container, a building material forming mold and a carbon curing box; the gas outlet end of the carbon dioxide storage container is fluidly connected to the gas inlet end of the primary mixing container, the gas outlet end of the primary mixing container is fluidly connected to the gas inlet end of the waste gas absorption tank; the slurry outlet end of the primary mixing container is fluidly connected to the slurry inlet end of the secondary mixing container; the slurry outlet end of the secondary mixing container is fluidly connected to the slurry inlet end of the building material forming mold; the carbide slag cement blank after demoulding the building material forming mold is transferred to the carbon curing box for carbon curing; Carbide slag and water are added to a primary mixing container, mixed and sealed to be allowed to stand to obtain a carbide slag suspension; in a sealed state, carbon-fixing gas containing carbon dioxide is introduced into the carbide slag suspension using a carbon dioxide storage container while stirring to carry out a carbon fixation reaction, and after the carbon fixation reaction is completed, a pre-carbonized carbide slag slurry is obtained; the waste gas discharged from the primary mixing container is introduced into a waste gas absorption tank; the pre-carbonized carbide slag slurry and cement slurry dry material are added to a secondary mixing container, mixed and stirred to obtain carbide slag cement slurry; the carbide slag cement slurry is injected into a building material molding mold for molding, and a carbide slag cement blank is obtained after demolding; the carbide slag cement blank is placed in a carbon curing box for carbon curing, and after the carbon curing is completed, a cement-based building material finished product is obtained.
[0023] The technical solution of the present invention achieves the following beneficial technical effects: 1. The present invention adopts a method of coordinating CO2 premixed carbide slag with carbon curing to prepare cement-based building materials. CO2 is absorbed and fixed during the CO2 mineralization premixed carbide slag process, and the CO2 can be effectively captured. The generated CaCO3 product can continue to play a role as a seed in the carbon curing process. During the carbon curing process, CO2 further undergoes a carbon solidification reaction with the hydration products in the cement and the incompletely reacted carbide slag. The combined action of the two carbon fixation methods can maximize the carbon fixation rate, and has a green and environmentally friendly carbon fixation effect.
[0024] 2. The present invention adopts carbide slag as an enhanced carbon-fixing material to improve the carbon-fixing efficiency of directly mixing CO2 with cement-based materials, which can avoid the problem of incompatibility with cement caused by directly adding carbide slag to cement, as well as the low solubility of CO2 during pre-carbonization and the low diffusion rate in cement particles. The principle is that Ca(OH)2 in carbide slag first reacts with CO2 to generate CaCO3. The generated CaCO3 greatly improves the mechanical properties of building materials products, not only can it achieve carbon emission reduction of greenhouse gases (industrial waste gas containing low concentration of carbon dioxide is directly utilized), but also effectively utilizes industrial solid waste, realizes the green concept of carbon fixation of solid waste and waste gas, and has great economic and social benefits.
[0025] 3. The present invention adopts the concept of synergistic preparation of low-carbon cement-based materials and resource utilization of carbide slag to solve the problem of low carbon fixation efficiency of CO2 on cement-based materials and resource utilization of carbide slag. Carbide slag is first used for CO2 premixing, and then the test piece made by mixing the premixed carbide slag with cement slurry is carbon-cured. This "pre-carbonization-re-carbonization" two-stage carbon fixation technology not only solves the problem of carbon emission reduction, but also effectively utilizes industrial solid waste and industrial waste gas (flue gas containing a lower concentration of carbon dioxide). The carbide slag cement-based environmentally friendly material in the present invention can not only promote the absorption and fixation of CO2, but also the CaCO3 generated in the CO2 premixing process and the carbon curing process increases the density of the building material, thereby improving the mechanical properties of the building material product. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the pre-carbonization reaction of carbide slag in an embodiment of the present invention; Figure 2 A device for preparing pre-carbonized carbide slag cement slurry in an embodiment of the present invention; Figure 3 The technical roadmap for preparing carbide slag cement-based building materials in the embodiment of the present invention; Figure 4 Relationship diagram between carbon curing time and carbon fixation rate under different pre-carbonization times in the embodiment of the present invention (10% carbide slag dosage); Figure 5 Relationship diagram between carbon curing time and carbon fixation rate under different pre-carbonization times in the embodiment of the present invention (with 20% carbide slag dosage); Figure 6 Relationship diagram between carbon curing time and carbon fixation rate under different pre-carbonization times in the embodiment of the present invention (30% carbide slag dosage); Figure 7 Relationship diagram between carbide slag dosage and compressive strength under different curing methods in the embodiment of the present invention.
[0027] The reference numerals in the figure are as follows: 1-carbon dioxide storage container; 2-flow controller; 3-magnetic stirrer; 4-rotor; 5-glass tube; 6-rubber hose; 7-temperature measuring rod; 8-wax seal; 9-CaCO3 precipitation; 10-NaOH solution; 11-carbide slag suspension. DETAILED DESCRIPTION
[0028] The method for preparing cement-based building materials using carbon dioxide precarbonized carbide slag in this embodiment comprises the following steps: Step 1: Mix carbide slag with water in a certain proportion and seal it for 10 minutes to obtain carbide slag suspension; Step 2: After sealing and standing, stir the carbide slag suspension at a speed of 600rpm, and diffuse the carbon-fixing gas (the carbon-fixing gas is the flue gas recovered from the cement plant, and its volume concentration of carbon dioxide is 20%) into the solution at a speed of 2 L / min through a glass tube, so that it absorbs and fixes carbon dioxide while stirring. The introduction time of carbon dioxide gas has three types: 10min, 20min or 30min. In addition, during the process of carbon dioxide precarbonization, it is necessary to use REX PHS-3C PH meter and DDS-11 conductivity meter to continuously test the changes in pH and conductivity of the precarbonized carbide slag suspension every 2min, and collect the carbon solidification product every 5min, vacuum filter, wash with ethanol 3 times, dry at 105℃ and perform XRD test to analyze the changes in mineral composition of the carbon solidification product with precarbonization time.
[0029] Step 3: Add the carbide slag suspension that has been pre-carbonized for 10 minutes, 20 minutes or 30 minutes into a pure slurry mixer, and add cement according to the amount in Table 1 and stir for 3 minutes to prepare carbide slag cement slurry. The mix ratio of pre-carbonized carbide slag cement slurry is shown in Table 1.
[0030] Table 1 Proportion of pre-carbonized carbide slag cement slurry In Table 1, the particle size range of carbide slag is 10-40 μm; the cement is ordinary Portland cement with a strength grade of 42.5.
[0031] Step 4: Inject carbide slag cement slurry into 100×100×100mm 3 The specimens were placed in a mold and demolded for standard curing and carbonization curing after 24 hours to obtain standard curing specimens and carbonization curing specimens respectively. The standard curing time was 28 days; the carbonization curing specimens were placed in a TH-B concrete carbonization test chamber under the conditions of 70% relative humidity, 20°C temperature, and 20% CO2 concentration for curing for 7 days, 14 days, and 28 days.
[0032] Step 5: Perform compressive strength tests on standard cured specimens and carbonized cured specimens at a loading speed of 2.4KN / m. The specific operation is carried out in accordance with the "Test Methods for Basic Properties of Building Mortar" (JGJ / T 70-2009). Perform a muffle furnace test on the carbonized cured specimens. First, slice the cured samples, about 30g, and then dry them at 65℃ for 3d. Finally, use a muffle furnace to heat to 520℃ and 950℃, measure the sample mass, and calculate the carbon fixation rate as follows: (1); (2); In the formula, a is the carbon fixation rate, m 520℃ Yes 520 ℃ The sample quality, m 950℃ Yes 950 ℃ The sample quality, m c and m ccs is the mass of cement (g) and carbide slag (g) in the sample, M max is the maximum theoretical carbon fixation rate, CaO, SO3, M g O, Na2O, and K2O represent the proportion of each mineral in cement and carbide slag (CCS), respectively. Table 2 shows the proportion of mineral composition of cement and carbide slag.
[0033] Table 2 Mineral composition ratio of cement and carbide slag The device for preparing cement-based building materials by using carbon dioxide precarbonized carbide slag in this embodiment comprises a carbon dioxide storage container, a primary mixing container, a waste gas absorption tank, a secondary mixing container, a building material forming mold and a carbon curing box, wherein the primary mixing container is a closed container; the gas outlet end of the carbon dioxide storage container is fluidly connected to the gas inlet end of the primary mixing container, the gas outlet end of the primary mixing container is fluidly connected to the gas inlet end of the waste gas absorption tank; the slurry outlet end of the primary mixing container is fluidly connected to the slurry inlet end of the secondary mixing container; the slurry outlet end of the secondary mixing container is fluidly connected to the slurry inlet end of the building material forming mold; the carbide slag cement blank after demolding the building material forming mold is transferred to the carbon curing box for carbon curing protection; adding carbide slag and water into a primary mixing container, mixing and sealing and standing to obtain carbide slag suspension; in a sealed state, using a carbon dioxide storage container to introduce carbon-fixing gas containing carbon dioxide into the carbide slag suspension while stirring to carry out carbon fixation reaction, and after the carbon fixation reaction is completed, pre-carbonized carbide slag slurry is obtained; the waste gas discharged from the primary mixing container is introduced into a waste gas absorption tank; the pre-carbonized carbide slag slurry and cement slurry dry material are added to a secondary mixing container, mixed and stirred to obtain carbide slag cement slurry; the carbide slag cement slurry is injected into a building material molding mold for molding, and a carbide slag cement blank is obtained after demoulding; the carbide slag cement blank is placed in a carbon curing box for carbon curing, and after the carbon curing is completed, a cement-based building material finished product is obtained.
[0034] For the preparation method of steps 1 to 3 above, the following method is used: Figure 2 The preparation device shown in the figure comprises a carbon dioxide storage container 1 and a flow control unit, the gas outlet of the carbon dioxide storage container 1 is connected by a pipeline, a flow control meter 2 is arranged on the pipeline, the device also comprises a primary mixing container (a magnetic stirrer 3, a rotor 4 and a beaker with a rubber stopper); the carbon dioxide that has not had time to react is discharged from a glass conduit 5, a rubber hose 6 that serves to connect the glass conduit, a conical flask is used as a waste gas absorption tank and contains a NaOH solution 10, which is used to absorb the carbon dioxide that has not had time to react, so as to achieve an environmental protection effect, a calcium carbide slag suspension 11 generated by pre-carbonization, and a CaCO3 precipitate 9. It should be noted that the test must be carried out in a sealed state, so a wax seal 8 must be carried out, and a temperature measuring rod 7 can be used to detect the temperature during the test.
[0035] In step 1 to step 5, the technical roadmap of pre-carbonization-re-carbonization two-stage carbide slag cement-based materials is as follows: Figure 3 As shown, in this embodiment, the secondary mixing container is a pure slurry mixer, the carbon curing box is a TH-B type carbonization box; the building material forming mold is 100×100×100mm 3 The box.
[0036] Figures 4 to 6 This is the relationship between different carbide slag dosage, pre-carbonization time, carbon curing time and carbon fixation rate. Figures 4 to 6It can be obtained that: when the dosage is constant, the carbon fixation rate gradually increases with the increase of carbon curing time and tends to be stable in the later period; the carbon fixation rate increases with the increase of pre-carbonization time; in addition, when the dosage of carbide slag increases from 10% to 20% and from 20% to 30%, the carbon fixation rate increases by 1.26 times and 1.21 times respectively. It can be found that with the increase of the dosage of carbide slag, the carbon fixation rate gradually increases, realizing the high-value utilization of bulk solid waste.
[0037] from Figures 4 to 6 It can also be seen that when the amount of carbide slag and the pre-carbonization time are constant, the carbon fixation rate increases with the increase of carbonization curing time, that is, the carbon fixation rate is the highest when the carbonization curing time is 28 days. Therefore, in this embodiment, the compressive strength of the test pieces prepared with different amounts of carbide slag and different pre-carbonization times was measured after 28 days of carbonization curing. The test results are shown in FIG. Figure 7 As shown. Figure 7 It can be seen from the data that with the increase of carbide slag content, the compressive strength of the specimens prepared under various conditions shows a decreasing trend; and the strength during the two-stage carbon fixation of pre-carbonization and carbon curing is higher than that of standard curing, indicating that the synergistic effect of CO2 premixed carbide slag and carbon curing can make up for the insufficient strength caused by the addition of carbide slag. The strength of premixing for 10, 20, and 30 minutes plus carbon curing for 28 days is 2.67 times, 2.90 times, and 1.30 times higher than that under standard curing conditions, respectively. Therefore, the synergistic effect of CO2 premixed carbide slag and carbon curing can significantly improve the compressive strength of the specimens.
[0038] In addition, when the pre-carbonization and carbon fixation reaction is carried out in step 2 of this embodiment, the carbon fixation conditions of carbon fixation gases with carbon dioxide concentrations of 40% and 60% are compared. The test results show that as the carbon dioxide concentration in the carbon fixation gas increases, the carbon fixation rate also increases, but the increasing trend is not obvious (so this part of the test content will not be repeated here). This also shows that under the process conditions of this embodiment, the use of low-concentration carbon dioxide as the carbon fixation gas for carbide slag carbon fixation to prepare cement-based building materials can achieve an ideal carbon fixation effect.
[0039] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.
Claims
1. A method for preparing cement-based building materials using carbon dioxide precarbonized carbide slag, characterized in that: The steps include: Step (1), mixing carbide slag with water and sealing and letting it stand to obtain a carbide slag suspension; Step (2), in a sealed state, introducing a carbon-fixing gas containing carbon dioxide into the carbide slag suspension while stirring to carry out a carbon-fixing reaction, and after the carbon-fixing reaction is completed, a pre-carbonized carbide slag slurry is obtained; Step (3), mixing the pre-carbonized carbide slag slurry with the cement slurry dry material to obtain carbide slag cement slurry; Step (4), injecting carbide slag cement slurry into a mold for molding, and obtaining carbide slag cement blank after demoulding; Step (5), placing the carbide slag cement blank in a carbon curing box for carbon curing, and obtaining a cement-based building material product after the carbon curing is completed.
2. The method for preparing cement-based building materials using carbon dioxide precarbonized carbide slag according to claim 1, characterized in that: In step (1), the particle size range of carbide slag is 5 to 75 μm; the mass ratio of carbide slag to water is 1:(1.5 to 5); and the sealed standing time is 10 to 20 minutes.
3. The method for preparing cement-based building materials using carbon dioxide precarbonized carbide slag according to claim 2, characterized in that: In step (1), the particle size range of carbide slag is 10 to 40 μm; the mass ratio of carbide slag to water is 1:2.5; and the sealed standing time is 10 minutes.
4. The method for preparing cement-based building materials using carbon dioxide precarbonized carbide slag according to claim 1, characterized in that: In step (2), during the carbon fixation reaction: the stirring rate is 600 to 800 rpm; the flow rate of the carbon fixation gas is 1.5 to 2.5 L / min; the carbon fixation reaction is carried out at room temperature; the carbon fixation reaction time is 10 to 30 min; and the volume concentration of carbon dioxide in the carbon fixation gas is greater than or equal to 20%.
5. The method for preparing cement-based building materials using carbon dioxide precarbonized carbide slag according to claim 4, characterized in that: In step (2), during the carbon fixation reaction: the stirring rate is 600 rpm; the flow rate of the carbon fixation gas is 2.0 L / min; the carbon fixation reaction time is 20 min; the carbon fixation gas is liquefied and purified carbon dioxide gas with a purity of 99.99% by volume; or, the carbon fixation gas is a mixture of liquefied and purified carbon dioxide gas with a purity of 99.99% by volume and air; or, the carbon fixation gas is flue gas recovered from a cement plant and / or a steel plant.
6. The method for preparing cement-based building materials using carbon dioxide precarbonized carbide slag according to claim 1, characterized in that: In step (3), the mass ratio of pre-carbonized carbide slag slurry to cement slurry dry material is 1: (0.8-1.5); the mixing time is 3-10 minutes; the cement slurry dry material is a composite material with cement as a cementitious material; the preparation method of the cement slurry dry material is: mixing and stirring the raw material components of the cement slurry dry material according to the designed ratio for 3-5 minutes.
7. The method for preparing cement-based building materials using carbon dioxide precarbonized carbide slag according to claim 6, characterized in that: In step (3), the mass ratio of the pre-carbonized carbide slag slurry to the cement slurry dry material is 1:1.14; the mixing time is 3 minutes; the cement slurry dry material is cement, cement mortar dry material or concrete dry material; the mixing time when preparing the cement slurry dry material is 3 minutes; The cement is ordinary Portland cement with strength grade 42.
5.
8. The method for preparing cement-based building materials using carbon dioxide precarbonized carbide slag according to claim 1, characterized in that: In step (4), the carbide slag cement slurry molding conditions are: demoulding after standing for 24 hours at room temperature and pressure; in step (5), the carbon curing conditions are: the volume concentration of carbon dioxide is 20±3%, the relative humidity is 70±5%, and the temperature is 20±3°C; the carbon curing time is 7 to 28 days.
9. The method for preparing cement-based building materials using carbon dioxide precarbonized carbide slag according to any one of claims 1 to 8, characterized in that: In step (1), the particle size of carbide slag is in the range of 10 to 40 μm; the mass ratio of carbide slag to water is 1:2.5; and the sealed standing time is 10 min; In step (2), during the carbon fixation reaction: the stirring rate is 600 rpm; the flow rate of the carbon fixation gas is 2.0 L / min; the carbon fixation reaction is carried out at room temperature; the carbon fixation reaction time is 20 min; the carbon fixation gas is flue gas recovered from a cement plant and / or a steel plant, and the volume concentration of carbon dioxide in the flue gas is 20%; In step (3), the mass ratio of the pre-carbonized carbide slag slurry to the cement slurry dry material is 1:1.14; the mixing time is 3 minutes; the cement slurry dry material is ordinary Portland cement with a strength grade of 42.5; In step (4), the carbide slag cement slurry is formed under the following conditions: standing at room temperature and pressure for 24 hours before demoulding; In step (5), the carbon curing conditions are: the volume concentration of carbon dioxide is 20%, the relative humidity is 70%, and the temperature is 20° C.; the carbon curing time is 28 days.
10. A device for preparing cement-based building materials using carbon dioxide precarbonized carbide slag, characterized in that: It includes a carbon dioxide storage container, a primary mixing container, a waste gas absorption tank, a secondary mixing container, a building material forming mold and a carbon curing box, wherein the primary mixing container is a closed container; the gas outlet end of the carbon dioxide storage container is fluidly connected to the gas inlet end of the primary mixing container, and the gas outlet end of the primary mixing container is fluidly connected to the gas inlet end of the waste gas absorption tank; the slurry outlet end of the primary mixing container is fluidly connected to the slurry inlet end of the secondary mixing container; the slurry outlet end of the secondary mixing container is fluidly connected to the slurry inlet end of the building material forming mold; after demoulding the building material forming mold, the carbide slag cement blank is transferred to the carbon curing box for carbon curing; Carbide slag and water are added to a primary mixing container, mixed and sealed to be allowed to stand to obtain a carbide slag suspension; in a sealed state, carbon-fixing gas containing carbon dioxide is introduced into the carbide slag suspension using a carbon dioxide storage container while stirring to carry out a carbon fixation reaction, and after the carbon fixation reaction is completed, a pre-carbonized carbide slag slurry is obtained; the waste gas discharged from the primary mixing container is introduced into a waste gas absorption tank; the pre-carbonized carbide slag slurry and cement slurry dry material are added to a secondary mixing container, mixed and stirred to obtain carbide slag cement slurry; the carbide slag cement slurry is injected into a building material molding mold for molding, and a carbide slag cement blank is obtained after demolding; the carbide slag cement blank is placed in a carbon curing box for carbon curing, and after the carbon curing is completed, a cement-based building material finished product is obtained.
Citation Information
Patent Citations
Method for preparing nano calcium carbonate by taking carbide slag as raw material
CN103738997A
Building material product prepared from building gypsum and carbide slag and preparation method thereof
CN108892467A
Acetylene sludge recycling process
CN109650429A
Method for preparing light calcium carbonate from carbide slag
CN110040757A
Method for preparing carbonated cementing material from carbide slag
CN110104970A